Kuzbass adapting to the global energy transition - Fridman Yuri; Rechko Galina; Loginova Ekaterina; Pimonov Aleksandr (E3S Web of Conferences, 2021)
The world energy system has entered the so-called energy transition stage, with decarbonization and the fight against climate change as drivers for change. This event may pose many grave dangers for the Russian coal industry and commodity-rich regions of the country, whose economy is based on coal mining. The authors rely on the research into the strategic development of Kuzbass, Russia’s major coal center, and discuss whether the state should actively participate in ensuring that the region adjusts to the terms of the energy transition.